JEWISH FAITH, TALMUD, AND ZIONIST IN ISLAMIC REVIEW - Meirison . .; Muhammad Ridho; Elfi Tajuddin; Zulfia Trinova (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Abstract: This paper aims to talk about the Talmud being the most important scripture for Jews, even more, important than the Torah. The author conducted a library study with a descriptive comparative approach to obtaining the Book of the Talmud not only became a source in the establishment of religious law but also became an ideology and principles, and a direction for the policy-making of the State and the Jewish government of Israel. More than that, Talmud became the view of the life of jews in general. That's also why the Jewish State of Israel is referred to as a racist, chauvinistic, theocratic, conservative, and highly dogmatic State. To understand the seemingly arrogant, stubborn, uncompromising State of Israel, one needs to understand the content of the Talmud's teachings, which the Jews believe to be the essential scripture among their scriptures. The Jews have made the Rabbis their own God in various aspects of life. Although Zionist Jews have turned secular, the Talmud continues to color the policies carried out by most Jews, especially Zionists.